The Community Transmigration Perceptions About The Important Of Informal Economy Education - Benedhikta Kikky Vuspitasari; Deffrinica Deffrinica; Laurensiana Albi (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to determine the perceptions of transmigration community regarding the importance of informal education especially in economy. This research is a descriptive qualitative research, considering that the object under study is the natural state of community perceptions, to describe the state of the population and to obtain data by using the method of observation, interviews and documentations. The data collection data is then compiled and analyzed by data reduction, data compilation, and drawing conclusions. From the results of the study it was found that, the transmigration community's perception of informal economic education starts from the family, namely parents as teachers who teach how children able to manages their finances wisely and responsibly so that, when a child getting adult they can be independent and able to manage finances as well apart from that Responsible for their own finances, the experiences gained from parents so that children can successfully manage their finances, through the values that must be possessed by a child to be able to improve the economy that is able to working hard, be brave, willing to developing, never give up, focus, save, live simply, move on, be able to read opportunities and save money by saving.